Perceptions of Young Teachers about the Issues Associated with Bringing out Model Schools in Tribal Areas - Pradhan, Manoranjan (JOURNAL OF INDIAN EDUCATION, 2014)
Koraput, a tribal dominated district, is one of the educationally backward districts in Odisha. The literacy rate of the district is far below the state and national average, and the dropout rate at schools is also higher than national level. To protect the interests of tribal children, both central and state governments have launched several schemes and projects for the educational upliftment of the people in the district but the actual socio-economic parameters present a gloomy picture. Recognising the significance of model teachers and schools in quality education, the present study intends to know the perceptions of the newly appointed young teachers of Koraput district about their schools and students. The study specially emphasises on identifying the issues and problems associated with the schools which restrict the teachers to make their schools model schools. Besides, the investigator tries to know the suggestive measures from the teachers directly in order to provide quality education to tribal children by making their schools as model, ideal, exemplary.